Post-crisis Shadow Banking system circumvention: banks and peer to peer industry upside Down in China - Di Hao (Program Pascasarjana STIE Amkop Makassar, 2021)
Abstract There are 10 developing and emerging members in 16 members of Regional Consultative Group for Asia. China provides one model from developing and emerging countries to harness shadow banks and fulfill the transformation of market-based finance. The financial policy uncertainty and delay stimulates shadow bank circumvention in the Chinese capital markets during 2010 and 2016. Inadequate regulatory regimes and underdeveloped infrastructure can not walk shoulder to shoulder with the economically booming shadow banking system in China. Two ways in the banking industry and peer to peer industry respectively rake in enormous profit by regulation arbitrage. Complex chains with off-balance sheet financial instruments, inter-bank products, credit alternatives, and small lenders are carried out for shadow money under regulatory oversight. This kind of shadow bank circumvent has undergone short rising and falling period from 2011 to 2019. Under the case study of China which has undergone a life cycle, three key recommendations are rapped to confront circumvent efficiently such as credit reference system, technology energization, and policy perfection. Keywords: arbitrage; circumvention; shadow bank; peer to peer